Effect of new neuronal growth factor on healing of sciatic nerve in rats. (December 2015) - Al-Dakheel, Dakheel A.; Sadat-Ali, Mir; Azam, Md Quamar; El-Shawarby, Mohammed
Abstract: Objective: The study aimed to investigate the effect of a new peptide new nerve growth factor (NNGF) on the healing of divided sciatic nerves in rats. Material and methods: Twenty Sprague–Dawley rats of 250–300 g were divided into two groups (group 1 — study group and group 2 — control group). Under ketamine intramuscular anesthesia sciatic nerves were exposed, divided and repaired using 10/0 dexon. Study animals had 10 mg/kg body weight of NNGF added to the repair. Electromyographic studies of the hind libs were carried out after 8 weeks. The average stimulation was 50 mA for 200 μS and four twitches (T) were recorded. The animals were euthanized and the sciatic nerves were removed for histological analysis. Results: There were no deaths in either of the groups. Electromyographic study showed that in the control group the average T1–T4 was 0.587 ± 0.17% and in the study group the average was 87.89 ± 5.02% (p value of 0.001). Histologically the control group showed regenerated axons sprouting from the proximal segment of cut nerve with empty endoneurial channels, while in the study group whole nerve trunks were seen within endoneurial channels. Conclusion: This study shows that the NNGF has a positive influence on the experimental healing of sciatic nerves in animals. Highlights: We have isolated an 8-amino acid polypeptide from human placenta. We tested the synthesized peptide in the divided sciatic nerves in rats. The results which included EMG and histopathological studies indicate that the peptide has a potential to heal neural tissue. The authors believe that more studies are needed probably in larger animals.